DATA MINING USING MULTIPLE LINEAR REGRESSION TO DETERMINE THE SUPPLY OF BUILDING MATERIALS - Vannia Wulandari; Hambali, Hambali; Ari Dermawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2026)
Abstract: This research is motivated by the problem of building material inventory management at Jaqfar Building Store, which is still done manually and based on subjective estimates. This often results in inaccuracies in determining stock levels, either in the form of overstock or understock, which hinders operational effectiveness. The purpose of this study is to apply the Multiple Linear Regression method to analyze the relationship between incoming stock (X1) and outgoing stock (X2) variables with the ending stock variable (Y) to produce an optimal inventory prediction model. The research methodology used includes collecting historical transaction data for building materials such as cement, ceramics, zinc, plywood, and iron. This web-based prediction system was developed using the PHP programming language and a MySQL database. The analysis results show that the resulting regression model can provide a mathematical picture of future inventory patterns based on historical data. Implementation of this system is expected to assist the management of Jaqfar Building Materials Store in making strategic decisions regarding purchasing and sales in a more measured and efficient manner. Keyword: building materials; data mining; inventory; multiple linear regression Abstrak: Penelitian ini dilatarbelakangi oleh permasalahan pengelolaan persediaan bahan bangunan di Toko Bangunan Jaqfar yang masih dilakukan secara manual dan berdasarkan perkiraan subjektif. Hal ini menyebabkan sering terjadinya ketidaktepatan dalam menentukan jumlah stok, baik berupa kelebihan barang (overstock) maupun kekurangan barang (understock) yang menghambat efektivitas operasional. Tujuan dari penelitian ini adalah menerapkan metode Multiple Linear Regression (Regresi Linear Berganda) untuk menganalisis hubungan antara variabel stok masuk (X1) dan stok keluar (X2) terhadap variabel stok akhir (Y) guna menghasilkan model prediksi persediaan yang optimal. Metodologi penelitian yang digunakan mencakup pengumpulan data historis transaksi bahan bangunan seperti semen, keramik, seng, triplek, dan besi. Sistem prediksi ini dikembangkan berbasis web menggunakan bahasa pemrograman PHP dan basis data MySQL. Hasil analisis menunjukkan bahwa model regresi yang dihasilkan mampu memberikan gambaran matematis mengenai pola persediaan di masa mendatang berdasarkan data historis. Implementasi sistem ini diharapkan dapat membantu manajemen Toko Bangunan Jaqfar dalam mengambil keputusan strategis terkait pembelian dan penjualan secara lebih terukur serta efisien. Kata kunci: bahan bangunan; data mining; persediaan; regresi linear berganda